2005
DOI: 10.2464/jilm.55.164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zr addition on microstructure of hot extruded P/M Al-Zn-Mg-Cu alloys

Abstract: In this study, the microstructure of hot-extruded and under-extruded Zr bearing aluminum alloys Mesoalite10 ®-1.3 mass%Zr was investigated by high-resolution EBSP analysis and the effect of Zr addition on microstructure formation during hot extrusion was studied. In an extruded Zr free alloy, coarse fibrous grains elongated to the extrusion direction were predominantly evolved. And these grains were considered to be formed by elongation of the original equi-axial grains by extrusion. Whereas, in extruded Meso1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Formation mechanisms of fine grains by continuous DRX are reported as follows. 8,12,13) Inhomogeneous local strains are induced by grain boundary shearing near grain boundaries of the initial coarse grain, and the local dislocation density increases. The dislocations are rearranged and a subboundary is formed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Formation mechanisms of fine grains by continuous DRX are reported as follows. 8,12,13) Inhomogeneous local strains are induced by grain boundary shearing near grain boundaries of the initial coarse grain, and the local dislocation density increases. The dislocations are rearranged and a subboundary is formed.…”
Section: Resultsmentioning
confidence: 99%
“…8) Microstructural observation using high-resolution EBSP analysis revealed that this increase was due to the addition of Zr, which promoted continuous dynamic recrystallization (DRX) under hot extrusion and thus the formation of a large number of fine grains. 8) This is believed to be the effect of Al 3 Zr particles, which precipitated during the degassing treatment involving Zr addition. However, it is not clear why the presence of Al 3 Zr particles promotes continuous DRX under hot extrusion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zr addition to Meso10 in supersaturation leads to continuous dynamic recrystallization (DRX) occurs during hot extrusion, and many fine grains with diameters of about 1 mm are formed [2]. It is thought that L1 2 -structured Al 3 Zr particles precipitate upon the addition of 1.3 mass% Zr during the degassing process before hot extrusion, and that these particles inhibit the migration of initial grains [3,4].…”
Section: Introductionmentioning
confidence: 99%